Business income dynamics and labor market fluidity - Henry R. Hyatt; Seth Murray; Kristin Sandusky (IZA Journal of Labor Economics, 2021)
The share of the U.S. population that receives business income has increased substantially in recent decades. At the same time, worker hire and separation rates declined, with worrying implications for productivity and wage growth. In this paper, we explore the relationship between business income (BI) receipt and labor reallocation. We show that BI recipients are largely excluded from existing measures of labor reallocation. Including BI recipients reduces the measured decline from 1994 to 2014 in the hire and separation rates by 8.3-8.7%, respectively, primarily among jobs that were secondary sources of income or short in duration. We present evidence that worker transitions between wage and salary jobs and BI represent labor reallocation, as opposed to reclassification of employees as independent contractors.
Keywords: J63; L26; 330; labor reallocation; employment dynamics; self-employment; business ownership